Teaching in inclusive school communities. - Carrington,Suzanne; Macarthur, Jude. (Australia : John Wily & sons, 2012)
This is the essential resource to provide pre-service teachers with the most contemporary, ethical and useful framework for incorporating diversity and inclusive practices in today's classroom. Fourteen concise chapters compose a focused picture of the values and beliefs that inform the inclusive education approach, with the most up-to-date connections to curriculum and pedagogy throughout. Complemented by the latest research in the field, this text provides the practical knowledge and skills needed for inclusive classroom teaching in Australia and New Zealand, as well as a thorough analysis of exactly what is required to build respectful relationships in modern school communities.
includes index.
Keywords: Inclusive education; Mainstreaming in education